The Effect of Gadget Use on Social Interaction Among Preschool Children in XYZ Sub-District, Surabaya - Yenny, Yenny Yenny; Nurul Suhesti; Nevrettia Christantyawati; R. Ayu Erni Jusnita; R. Hartopo Eko Putro (PT. Banjarese Pacific Indonesia, 2025)
This research examines the impact of gadget use on early childhood social interaction within the urban setting of XYZ Village, Surabaya, amid the growing prevalence of digital exposure among young children. Anchored in Vygotsky’s Sociocultural Theory and the Socialisation Theory, the study evaluates how the duration and frequency of gadget use influence key social competencies, including verbal communication, cooperative behavior, and empathy in children aged 3 to 6 years. Employing a quantitative, cross-sectional design, the study collected data from 100 children using parent-administered questionnaires and direct observational methods, followed by analysis through multiple linear regression. The findings demonstrate that both the duration and frequency of gadget use exert a statistically significant influence on children’s social interaction (p < 0.05), accounting for 19% of the variance (R² = 0.190). The remaining variation is likely influenced by external variables such as parenting styles, digital content quality, and psychological factors. These outcomes underscore the importance of regulated gadget use, active parental involvement, and integrative educational practices that promote both digital literacy and interpersonal development.